THE PREMISES OF FORMATION OF ECO-CONSCIOUS LITERATURE IN THE MEKONG DELTA IN SOUTHERN VIETNAM - Pham Thi, Luong (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
In the first twenty years of the twenty-first century, ecological literature in the Mekong Delta appeared in many works with typical genres such as poetry and short stories. Many writers and poets are concerned about the reality of the environment in the delta, so they have integrated and included issues with a clear ecological consciousness in their works. To answer the question of why eco-conscious literature appeared in the Mekong Delta, the article focuses on explaining the issues of natural, social, and cultural conditions and environmental changes. As ecology affects the sense and responsibility of writers, this article shows that each region with different natural, cultural and social conditions has a more or less impact on the formation of literary characteristics in each region, especially for eco-conscious literature. A literary work expressing ecological consciousness often refers to environmental changes that have a negative impact on human life. The literary works relating to this issue mainly mention the consequences that people have suffered from climate change, soil, water, air, and flora or reveal people’s attitudes and feelings towards the situation they are witnessing. Therefore, the natural, cultural and social conditions and their changes directly affect the formation of a part of literature with ecological consciousness in this area.